Effect of acid-base changes on urinary hydrolases in Fabry's disease after renal transplantation - Berty, R M; Adler, S; Basu, A; Glew, R H (The Journal of laboratory and clinical medicine, 1990)
Fabry's disease, which is characterized by alpha-galactosidase A (AG) deficiency, causes early renal failure. Kidney transplants do not reliably supply the deficient enzyme. To assess both urinary excretion of AG by the transplant and the relationship between urine and serum hydrolase activity, acute and chronic acid-base studies were performed in normal control subjects and in the patient with Fabry's disease who had undergone renal transplantation. For the acute studies, alkalosis was induced by intravenous infusion of sodium bicarbonate and acidosis was induced by ingestion of ammonium chloride. The chronic study involved long-term ingestion of NH4Cl by only the patient with Fabry's disease. The results show that AG is secreted by the renal graft. Urinary hydrolase excretion was increased by acute alkalinization and decreased by acute acidification. Acute, but not chronic, acidification increased the patient's serum AG activity, indicating that long-term acidification is not useful for treating Fabry's disease after transplantation. The large changes in hydrolyase excretion induced by acute and chronic acid-base changes show the difficulty of using lysosomal enzymuria as a diagnostic marker for renal disorders without knowledge of acid-base conditions.